Evaluating the Use of the Activity Based Costing Method in the Construction Industry in the V4 Countries - Hudáková Stašová, Lenka (International Journal of Industrial Engineering and Management, 2019)
This paper evaluates the situation regarding the use of the Activity Based Costing calculation method in the sphere of industry construction in the V4 countries at the present time. The objective of the paper is to describe the strengths and weaknesses of the ABC method in comparison with the traditionally used method of allocating costs, analyse the use of calculation methods in the construction industry in the Slovak Republic, the Czech Republic, Hungary and the Republic of Poland, and present recommendations on the basis of the analysis results. In the paper we describe the current trends in the construction industry, the conditions for suitability of implementation of the ABC method, the possibilities of its use in company practice. The ABC method is more accurate than the traditional calculation methods, so we would recommend companies which do not have the costing method in place should consider the possibility of using the method, despite the initial high deployment costs. In companies where the overhead cost ratio is more than 40% of the total cost, the traditional costing method is not sufficient to accurately allocate indirect costs, and therefore we recommend that an ABC method be used for such businesses. ABC focuses mainly on the precise allocation of overheads, thus achieving an accurate tracking of the flow of costs and their causes, reducing the resources used and reducing overall costs. We prepared our own questionnaire for analysis. The questions were answered by the company workers who do cost calculations and who are responsible for the cost calculations. The survey was conducted at company level. The total group of companies from 4 countries represented 204 companies. We also evaluated the results statistically. We focused the analysis on construction industry companies as one of the key sectors of the economy. We highlighted the benefits of the Activity Based Costing method, the study was focused on the construction industry. But similar conclusions could be applied to other industries as this method is flexible, adaptable to different environments, adaptable to different company sizes. Article history: Received (30-APR-2019); Revised (18-SEP-2019); Accepted (2-OCT-2019); Published online (8-OCT-2019)